HUBUNGAN JOB DEMANDS DENGAN WORK ENGAGEMENT PADA PNS BALAI BESAR POM DI MEDAN - Cintia M F Lumban Gaol; Nenny Ika Putri Simarmata (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Employee work engagement plays a pivotal role in sustaining the quality and effectiveness of public services, while increasing job demands may shape the extent to which employees remain psychologically connected to their work. Within government institutions, however, evidence regarding the association between job demands and work engagement remains inconsistent, particularly in organizations responsible for regulatory oversight and public service, such as the National Agency of Drug and Food Control. This study examined the relationship between these two variables among Civil Servants employed at the Medan Center for Food and Drug Control using a quantitative correlational design. The study involved the entire population of 127 employees through a total sampling technique. Data were collected using the Job Demands Scale and the Work Engagement Scale, and analyzed through normality and linearity tests followed by the Pearson Product-Moment correlation using IBM SPSS Statistics 26.0. Descriptive findings indicated that most participants reported low levels of job demands and high levels of work engagement. Correlation analysis yielded a coefficient of r = −0.280 with a significance value of p = 0.001 (p < 0.05), indicating a significant negative relationship between the two variables. These findings contribute additional empirical evidence concerning the interplay between job demands and employee engagement in the public sector while providing practical insights for developing human resource management strategies aimed at sustaining employees' work engagement. ABSTRAK Keterikatan pegawai terhadap pekerjaan menjadi salah satu elemen yang menentukan keberhasilan penyelenggaraan layanan publik, sementara tuntutan pekerjaan yang terus berkembang dapat memengaruhi kualitas keterlibatan tersebut. Pada lingkungan instansi pemerintah, hubungan antara job demands dan work engagement masih memperlihatkan temuan yang beragam, khususnya pada organisasi yang memiliki karakteristik tugas pengawasan dan pelayanan seperti Balai Besar POM. Penelitian ini mengeksplorasi keterkaitan kedua variabel tersebut pada Pegawai Negeri Sipil (PNS) Balai Besar POM di Medan melalui pendekatan kuantitatif dengan desain korelasional. Seluruh populasi yang berjumlah 127 pegawai dilibatkan sebagai responden menggunakan teknik total sampling. Data diperoleh melalui Skala Job Demands dan Skala Work Engagement, kemudian dianalisis menggunakan uji normalitas, uji linearitas, serta korelasi Pearson Product Moment berbantuan IBM SPSS Statistics 26.0. Gambaran deskriptif menunjukkan bahwa sebagian besar responden berada pada kategori job demands rendah dan work engagement tinggi. Analisis korelasi menghasilkan koefisien sebesar r = −0,280 dengan nilai signifikansi p = 0,001 (p < 0,05), yang mengindikasikan adanya hubungan negatif dan signifikan antara kedua variabel. Temuan ini memperluas bukti empiris mengenai dinamika tuntutan kerja dan keterikatan pegawai pada sektor pemerintahan sekaligus memberikan landasan bagi penguatan strategi pengelolaan sumber daya manusia untuk mempertahankan tingkat work engagement secara berkelanjutan.